Expression of ompR gene in the acid adaptation and thermal resistance of Salmonella Enteritidis SE86 - Ritter, Ana Carolina; Bacciu, Donatella; Santi, Lucelia; Rubino, Salvatore; Uzzau, Sergio; Tondo, Eduardo Cesar (The Journal of Infection in Developing Countries, 2014)
Introduction: The objective of this study was to evaluate the involvement of the ompR gene in the acid adaptation and thermal resistance of S. Enteritidis SE86, responsible agent of more than 95 % of investigated food-borne diseases, throughout the last decade in Southern Brazil. In this study, we constructed a mutant strain of S. Enteritidis SE86 (ΔompR) that was attenuated by a knockout technique. The OmpR protein expression was determined in a tagged (3XFLAG) strain of S. Enteritidis SE86. Methodology: The mutant strains were cultivated separately in nutrient broth and nutrient broth supplemented with 1% glucose (NBG) to induce acid adapted cells. The organisms were exposed to different temperature such as 37 ºC, 52 ºC, and 60ºC. The survival of the SE86 wild type (WT) and attenuated strain was determined by bacterial count, and the tagged protein (ompR::3XFLAG cat::FLAG) was detected by SDS-PAGE and immunoblotting with anti-FLAG antibodies. Results: Results showed that when exposed at 52ºC, the acid-adapted SE86 WT cells were completely inactivated after 300 minutes; however, non-adapted cells (WT and ΔompR) and acid-adapted ΔompR demonstrated higher thermal sensitivity, since they were completely inactivated in 240 minutes. At 60ºC, the acid-adapted SE86 ΔompR also demonstrated higher sensitivity that SE86 WT, being totally inactivated after 15 minutes, while the WT cells were inactivated in 20 minutes. Conclusion: The acid adapted cells showed increased expression of OmpR when exposed to 52 ºC and 60ºC, this confirmed the requirement of acid adaptation for S. Enteritidis SE86 to resist elevated temperatures.